Building replicated database systems using distributed shared memory - Duarte Filho, Nelson Lopes (2015)
Submitted by Eliezer Mendes Lopes (mendesfurg@gmail.com) on 2015-05-16T00:36:05Z No. of bitstreams: 1 BUILDING REPLICATED DATABASE SYSTEMS USING DISTRIBUTED SHARED.pdf: 1763590 bytes, checksum: 80be0aaddec7449d6370f746112ed805 (MD5)